História, filosofia, ensino de ciências e formação de professores: desafios, obstáculos e possibilidades - André Ferrer P. Martins (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
The History and Philosophy of Science (HPS) achieved a prominent role in the field of Science Teaching. However, difficulties remain concerning the use of historical and philosophical elements in teaching and science teachers´ education. The present study addresses this theme and it is divided into two parts. At first, we make a brief review of two empirical studies. One study was conducted with teachers and future teachers of Physics, and it indicates the nature of the obstacles currently encountered to the use of HPS for didactic purposes. The other study sought to carry out a comparative analysis between historical-philosophical disciplines in two teacher education undergraduate courses. In the second part of this work, we argue that a possible way to overcome some difficulties regarding the inclusion of HPS in teaching is working with "episodes" that promote meaningful discussions about the nature of science. We report the dynamics of a course addressed to high school physics teachers in the city of Natal (RN), dedicated to the discussion of two episodes from the history of mechanics. Our findings point to a complex scenario of problems to be faced in working with HPS in teaching and teacher education.